A systematic review of the assessment of out-of-pocket payment removal policies in reducing the economic burden caused by direct and indirect costs of HIV service utilization in South Africa - Majokweni, Hlombekazi (Department of Public Health and Family Medicine, 2026)
Background: The call for universal health coverage (UHC) has led to some policy introductions such as the removal of out-of-pocket payments (OOPs) in the form of user fees at point of care in primary health facilities in South Africa. The cost of healthcare for patients is not only a barrier to access and utilisation but can also lead to catastrophic spending and impoverishment. For people living with HIV (PLWH), health expenses can threaten their financial wellbeing due to HIV treatment requiring multiple health visits and other healthrelated costs. We examine how the UHC policy of user fee removal has contributed to reducing the economic burden of HIV/AIDS for PLWH and their households. Methods: Searches were conducted on Africa Wide, CINAHL, EconLit, Health Source, PsycInfo, PubMed and Web of Science. We included quantitative and qualitative articles that reported costs of HIV service utilization or reported impoverishment and catastrophic health expenditure (CHE) as part of their outcomes. We reviewed and extracted data that would assist in answering the review question and reported on the total cost of utilization and its impact on PLWH. Results: We found 12 eligible articles. The reviewed data showed that PLWH spent a substantial amount of money on transport, additional care such as private doctors, traditional healers, and special food showing that user fee removal alone is insufficient for financial protection. People borrowed money, took interest bearing loans and sold assets to cover healthcare expenses. PLWH experienced CHE across various thresholds, and people in the rural areas had more odds of CHE compared to those in urban areas. Additional care outside of the public health system and transport were drivers of CHE and impoverishment. Conclusion: The UHC policy of user fee removal at point of care has been beneficial in reducing the economic burden of HIV/AIDS service utilization for people living in close proximity to the primary healthcare facilities and those who receive care in well-resourced facilities. However, the same cannot be said about those who have to travel long distances to health facilities and are forced to seek additional care for their health needs to be sufficiently met.